The acute effects of combined supplementation of beta-alanine, carbohydrate and whey protein on biochemical parameters of athletes after exhaustive exercise - Mor, Ahmet; İpekoğlu, Gökhan; Arslanoğlu, Erkal; Arslanoğlu, Cansel; Acar, Kürşat (Progress in Nutrition, 2018)
Background: The beneficial effect of popular supplements and use of combined supplementation in athletes which purpose to increase sports performance. Objective: This study aimed to review biochemical responses that the athletes gave to combined supplementation received after exercise and some changes in hematological values. Material and Method: 16 volunteers, in shape, male athletes with ages between 18-25 participated into the study. Athletes were divided into two groups as experiment (supplement) (n=8) and control (placebo) (n=8). After the exercise made until exhaustion (shuttle run test), beta-alanine/vitargo(carbohydrate-electrolyte)/whey protein supplement was given to the experimental group while the control group received placebo (water). Blood was taken from the athletes three times as basal, post-exercise (PE) and 2 hours after ingestion supplement (PS); Urea, Creatinine, Cholesterol, Triglyceride, High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL), Gamma Glutamyl Transferase (GGT) and Alkaline Phosphatase (ALP) values have been analyzed. Results: Statistically significant differences in many biochemical parameters were found when comparisons of in-group basal, PE and PS time courses of supplement and control groups were reviewed (p